SSARP: a sound speed adaptive routing protocol for large–scale underwater acoustic sensor networks. (26th August 2014) - Chen, Yen–Da; Li, Chun–Chih; Lien, Chan–Ying; Wang, Ching–Hung; Shih, Kuei–Ping
In this paper, an important property of acoustic signal that the speed of acoustic signal varies with water depth has been considered to explore a new routing protocol in UASNs. It implies that the shortest end–to–end delay path may not be the shortest path directly from the source to the sink. Based on this property, a per–hop based routing protocol, named sound speed adaptive routing protocol (SSARP), is proposed. SSARP takes the acoustic speed in different water depth into consideration. SSARP can find a path with a short end–to–end delay to transmit the data. The simulation results also verify that SSARP actually reduces the end–to–end delay and outperforms other routing protocols in terms of end–to–end delay.